If you mean: (x+3) squared = (x+2) squared +11 Then the value of x works out as 3
(5x + 2)(x + 3)
7(3y-2)-(-4y+9)
1 squared radical 40 is equal to 1 squared radical (4 x 10), and this become 2 squared radical 10. By adding 2 squared radical10 with 3 squared radical 10 we get 5 squared radical 10.
9x squared plus 16 = 0 factored is plus and minus 4/3 i.
104
7^2 + 3^2 = 58
When the sum of a number plus 3 is squared, it is 11 more than the sum of the number plus 2 when squared.
if it is not this . -3<x<-2 < or equal
3
2
2
2
2
If you mean: (x+3) squared = (x+2) squared +11 Then the value of x works out as 3
3
3² + 20 ÷ 2² = 9 + (20 ÷ 4) = 14.